The effects of peculiar velocities in SN Ia environments on the local H0 measurement. Issue 3 (7th November 2020) - Sedgwick, Thomas M; Collins, Chris A; Baldry, Ivan K; James, Philip A
ABSTRACT: The discrepancy between estimates of the Hubble constant ( H 0 ) measured from local ( z ≲ 0.1) scales and from scales of the sound horizon is a crucial problem in modern cosmology. Peculiar velocities ( v pec ) of standard candle distance indicators can systematically affect local H 0 measurements. We here use 2MRS galaxies to measure the local galaxy density field, finding a notable z < 0.05 underdensity in the SGC-6dFGS region of 27 ± 2 per cent. However, no strong evidence for a 'Local Void' pertaining to the full 2MRS sky coverage is found. Galaxy densities are used to measure a density parameter, Δ ϕ +−, which we introduce as a proxy for v pec that quantifies density gradients along a supernova (SN) line of sight. Δ ϕ +− is found to correlate with local H 0 estimates from 88 Pantheon Type Ia supernovae (SNe Ia; 0.02 < z < 0.05). Density structures on scales of ∼50 Mpc are found to correlate strongest with H 0 estimates in both the observational data and in mock data from the MDPL2-Galacticus simulation. Using trends of H 0 with Δ ϕ +−, we can correct for the effects of density structure on local H 0 estimates, even in the presence of biased v pec . However, the difference in the inferred H 0 estimate with and without the peculiar velocity correction is limited to < 0.1 per cent. We conclude that accounting for environmentally induced peculiar velocities of SN Ia host galaxies does not resolve the tension between local and CMB-derived H 0 estimates.